Characterization of fiber reinforced nanohybrid dental composites from agricultural biowaste using kenaf fiber - Abbas, Hina (2022)
Background: Fiber reinforced composite was introduced due to development of new biomaterials, technological advancements, and more effective treatment approaches. Aims of the study: This study aimed to determine the bonding mechanism between kenaf fibers and nanohybrid dental composite derived from agricultural biowaste. The kenaf fiber reinforced composite was investigated for flexural and compressive strength. The features of fractured surface of the flexural specimens were also assessed. Materials and method: Preparation of kenaf fiber reinforced composite was done using the treated silica from rice husk and kenaf cellulose. The kenaf cellulose was processed and treated using tetraethyl orthosilicate (TEOS) sol gel. Fourier- transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) were used to investigate the treated kenaf cellulose. Six specimens were prepared for each group; composite groups A, B, C, D, E, F, G with 0%, 1% untreated, 2% untreated, 1% treated, 2% treated kenaf cellulose, Neofil and ever-X composite respectively. For compressive and flexural strength tests, specimens were formed using stainless steel molds with dimensions of 6mm x 4mm and 25mm x 2mm x 2mm, respectively. After light curing using a light cure unit (Elipar Deep cure L, 3M, USA) for 40 seconds, the specimens were tested using an Instron Universal Testing Machine (Shimadzu, Japan). SEM was used to examine the fractured flexural strength samples. Results: SEM showed the average diameter of treated kenaf fibers was 7.4μm whereas the average length of treated kenaf fibers was 537μm. The FTIR results suggested formation of chemical bonds between the kenaf cellulose and silica from TEOS sol gel. For flexural and compressive strength tests, one way ANOVA showed there was statistically significant difference (P<0.05) between all groups. The nanohybrid composite incorporated with treated kenaf cellulose resulted in comparable compressive strength with the commercial Neofil composite and no improvement for flexural strength. SEM analysis showed smoother fiber surface with presence of lesser voids and gaps between matrix and kenaf fiber which suggested enhanced interfacial bonding. Conclusion: Surface treatment of the kenaf cellulose improved the bonding mechanism in the kenaf reinforced nanohybrid composite. Adaptation between surface treated kenaf fiber and composite matrix contributed to improvement in compressive strength of fiber reinforced composite.